Original research: longitudinal evaluation of cognitively demanding daily function using performance-based functional assessment highlights heterogeneous trajectories in cognitive and functional abilities in people with Parkinson’s disease - Carlisle, Tara C.; Fought, Angela J.; Olson, Kaitlin E.; Lopez-Esquibel, Natalie; Simpson, Abigail; Medina, Luis D.; Holden, Samantha K. (Frontiers in Neuroscience, 2023)
Background: Longitudinal assessment of functional abilities in Parkinson’s disease (PD) is needed to determine the efficacy of cognitive interventions in providing meaningful improvements in daily life. Additionally, subtle changes in instrumental activities of daily living may precede a clinical diagnosis of dementia and could aid earlier detection of and intervention for cognitive decline. Objective: The primary goal was to validate the longitudinal application of the University of California San Diego Performance-Based Skills Assessment (UPSA). An exploratory secondary goal was to determine whether UPSA may identify individuals at higher risk of cognitive decline in PD. Methods: Seventy participants with PD completed the UPSA with at least one follow-up visit. Linear mixed effects modeling was used to identify associations between baseline UPSA score and cognitive composite score (CCS) over time. Descriptive analysis of four heterogeneous cognitive and functional trajectory groups and individual case examples was performed. Results: Baseline UPSA score predicted CCS at each timepoint for functionally impaired and unimpaired groups (p<0.01) but did not predict the rate change in CCS over time (p=0.83). Participants displayed heterogenous trajectories in both UPSA and CCS during the follow-up period. Most participants maintained both cognitive and functional performance (n=54), though some displayed cognitive and functional decline (n=4), cognitive decline with functional maintenance (n=4), and functional decline with cognitive maintenance (n=8). Conclusions: The UPSA is a valid measure of cognitive functional abilities over time in PD. Given the heterogeneity of functional and cognitive trajectories, this performance-based assessment did not predict cognitive decline with this relatively short follow-up. Further work is needed to understand longitudinal functional assessments in PD-associated cognitive impairment.